N6-methyladenosine RNA is modified in the rat hippocampus following traumatic brain injury with hypothermia treatment - Cheng, Jin; Lin, Lian; Yu, Jiangtao; Zhu, Xiaolu; Ma, Haoli; Zhao, Yan (Frontiers in Neuroscience, 2023)
Recent studies have suggested a role for N6-methyladenosine (m6A) modification in neurological diseases. Hypothermia, a commonly used treatment for traumatic brain injury, plays a neuroprotective role by altering m6A modifications. In this study, methylated RNA immunoprecipitation sequencing (MeRIP-Seq) was applied to conduct a genome-wide analysis of RNA m6A methylation in the rat hippocampus of Sham and traumatic brain injury (TBI) groups. In addition, we identified the expression of mRNA in the rat hippocampus after TBI with hypothermia treatment. Compared with the Sham group, the sequencing results of the TBI group showed that 951 different m6A peaks and 1226 differentially expressed mRNAs were found. We performed cross-linking analysis of the data of the two groups. The result showed that 92 hyper-methylated genes were upregulated, 13 hyper-methylated genes were downregulated, 25 hypo-methylated genes were upregulated, and 10 hypo-methylated genes were downregulated. Moreover, a total of 758 differential peaks were identified between TBI and hypothermia treatment groups. Among these differential peaks, 173 peaks were altered by TBI and reversed by hypothermia treatment, including Plat, Pdcd5, Rnd3, Sirt1, Plaur, Runx1, Ccr1, Marveld1, Lmnb2, and Chd7. We found that hypothermia treatment transformed some aspects of the TBI-induced m6A methylation landscape of the rat hippocampus.